PROFIL LULUSAN (TRACER STUDY) PROGRAM STUDI PENDIDIKAN EKONOMI YANG BEKERJA DI DUNIA USAHA DAN INDUSTRI 2000 – 2005 - Ngadiman Ngadiman (Jurnal Pendidikan Akuntansi Indonesia, 2008)
The aim of this research is to know the profile of grad of Economic Education Program FKIP UNS evaluated from the aspect of stakeholder. Population in this research is all consumer of grad of Economic Education Program FKIP UNS from year grad 2000 up to 2005. Data collected represent consisted of the data having the character of quantitative and qualitative. All data obtained can express the profile of grad of Economic Education Program [of] FKIP UNS especially related to area of their performance and work. Source of data in this research is consumer of grad of Economic Education Program FKIP UNS 2000 up to 2005. From case result of study of year detection 2003 to three sector becoming consumer of grad of Economic Education Program FKIP UNS  in the reality obtained  the following result: (1) 70% from grad put hand to the education sector, (2) 15% from grad put hand to the sector business, (3) 15% from grad put hand to the sector banking. Ability which is  assuming less mastered the collegiate, that is (1) 28,5% English And Computer, (2) 28,5% English And Leadership, (3) 28,5% Computer And Leadership, (4) 14,5% English While from result of detection study to seven institution of consumer of grad of Economic Education Program FKIP UNS in the reality all overall head express that collegiate performance is goodness